ALIH FUNGSI LAHAN SUBAK SABA DI DESA ADAT TAMBAWU KAJA KELURAHAN PENATIH DENPASAR TIMUR - Adhitya Wiguna, Anak Agung Gede; Kebayantini, Ni Luh Nyoman; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The land function change is one of causes of decreased green land particularly in Denpasar city; as occurred in one of green land at Tambawu Kaja Village that is Subak Saba. Subak Saba is one of green field that has function changed and nowadays there are buildings among the land. The problem of this research were: 1). How is the process of land function change at Subak Saba Tambawu kaja Village, 2) What is the reasons of land function change at Subak Saba in Tambawu Kaja Village, 3) How is the effect of agricultural land function change for farmer’s life of Subak Saba in Tambawu Kaja Village. The aim of this research was to identify the answers of the problems by using qualitative method.The theory used in this research was the theory of social change (evolution theory) proposed by Herbert Spencer. The results showed that the land function change due to the uncontrolled population growth and it was followed by increasing economic needs, this is the cause of community began to sell their land, thus the agricultural land in Denpasar especially Subak Saba is shrink. The emerged effect was the conversion of land function change impact at Subak Saba that changes both in subak members and people who have a field at Subak Saba. The conclusion was the land function change at Tambawu Village, East Denpasar is occurred. Keyword: Land Function Change